Nutrients foliar content for high productivity cultivars of guava in Brazil - Natale, W. [UNESP]; Coutinho, E. L M [UNESP]; Pereira, F. M. [UNESP]; Boaretto, A. E. (My University, 2002)
Commonly grown in tropical and sub-tropical regions, guava (Psidium guajava L.) is an important fruit crop of Brazil. It is cultivated on a large scale in São Paulo state, and covers about 6,500 hectares. As a result of the guava selection program developed at FCAV/UNESP, two new cultivars were created: 'Rica' and 'Paluma' with a high productivity, and also with higher nutritional requirement. Leaves analysis has become a powerful tool in mineral-nutrition research with fruit crops, not only to determine response to different nutrients, but also for diagnostic techniques in making fertilizer recommendations and assessing deficiency symptoms. Nutrient composition of the leaves varies depending on the leaf maturity, tree age, variety and nutrient supply. For the interpretation of analytical values, selection of the index tissue is important. The results of experiments conducted in the field during 1989-2000 were studied. The nutritional status was evaluated by annual leaf sampling, carried out at full bloom. Recent fully developed leaves, corresponding to the third pair (with the petiole) were collected, starting at the end of the branch, all around the tree, at a height of 1.5 m from the soil, with a total of 30 leaf pairs per sample. The yield was evaluated by weighing all the fruits in the useful area of each lot. Foliar chemical analysis showed excellent correlation with the fruit production. Through the results it was verified that the maximum yield was associated to the following levels: N = 22-26; P = 1.5-1.9; K = 17-20; Ca = 11-15; Mg = 2.5-3.5; S = 3.0-3.5 g kg -1; B = 20-25; Cu = 10-40; Fe = 50-150; Mn = 180-250; Zn = 25-35 mg kg-1 DW in the leaves of the 'Rica' guava and to N = 20-23; P = 1.4-1.8; K = 14-17; Ca = 7-11; Mg = 3.4-4.0; S = 2.5-3.5 g kg-1; B = 20-25; Cu = 20-40; Fe = 60-90; Mn = 40-80; Zn = 25-35 mg kg-1 DW in the leaves of the 'Paluma' guava.
Keywords: Foliar nutrition; Fruit crop; Orchard; Psidium guajava; Tropical fruit